2022
DOI: 10.3389/fmolb.2022.865833
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Alginate-Based Nanomaterials in Enhancing the Therapeutic Effects of Bee Products

Abstract: Since the ancient times, bee products (i.e., honey, propolis, pollen, bee venom, bee bread, and royal jelly) have been considered as natural remedies with therapeutic effects against a number of diseases. The therapeutic pleiotropy of bee products is due to their diverse composition and chemical properties, which is independent on the bee species. This has encouraged researchers to extensively study the therapeutic potentials of these products, especially honey. On the other hand, amid the unprecedented growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 259 publications
(357 reference statements)
0
12
0
Order By: Relevance
“…9,17,18 or with modified formulations as honey chitosan-based 19 or alginate-based hydrogel. 20 While propolis topical dressing 21 or its extract was used in either ointment formulation. 22 The topical application of propolis extract gel increases the expression of FGF-2 and fibroblasts within the traumatic ulcer healing process, 23 absolute ethanolic extract propylene glycol preparation dressing 24 or even wound spray 15,24 since these api products contain compounds with anti-bacterial, anti-oxidant, anti-inflammation, immunomodulation activity as well as collagen matrix production.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,17,18 or with modified formulations as honey chitosan-based 19 or alginate-based hydrogel. 20 While propolis topical dressing 21 or its extract was used in either ointment formulation. 22 The topical application of propolis extract gel increases the expression of FGF-2 and fibroblasts within the traumatic ulcer healing process, 23 absolute ethanolic extract propylene glycol preparation dressing 24 or even wound spray 15,24 since these api products contain compounds with anti-bacterial, anti-oxidant, anti-inflammation, immunomodulation activity as well as collagen matrix production.…”
Section: Introductionmentioning
confidence: 99%
“…69 Just wound develops, platelets and neutrophils infiltrate the injury site initiates mediator cytokines mediators 54 and create contact with exposed collagen and extracellular matrix (ECM) components to form a fibrin clot. 64 Immunomodulatory action of honey 20,37,64 and propolis 37,67 is widely discussed since successful api-treatment of a broad range of wound types particularly those chronic infected forms 49 for wounds with impaired healing, including delayed acute injuries and chronic injuries 70 which often stems from a dysregulated immune response initiated or exacerbated by existing comorbidities, multiple tissue injury or wound contamination 64 especially diabetic foot. 24 70-73 where diabetic patients, it have shown that honey can reduce serum TNF-α, IL-6, IL-1ß and TGF-ß by inhibiting NF-Kß.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations